MONEY, STOCK PRICES AND ECONOMIC ACTIVITY IN SELECTED EUROPEAN COUNTRIES - Kulhánek, Lumír (Journal of Advanced Studies in Finance, 2011)
The behavior of stock market prices and macroeconomic variables are a subject of investigations both of policymakers and also economists. This paper is concerned with causal linkages among money supply, output and stock price development in the selected European countries. The main objective is to investigate and evaluate long-run equilibrium relationships between macroeconomic variables and stock prices as well as shortrun dynamics using both the Vector Autoregressive (VAR) and Vector Error Correction (VEC) models in the analyzed countries. The emphasis of this paper in addition to evidence presented is garnered from the Euro-area and six EU-counties: the Czech Republic, Poland, Slovak Republic, Austria, Germany and the United Kingdom. Money supply M2, national stock market indices and real gross domestic product are used in this study. In the analysis, quarterly data in the sample period from 1995:Q1 to 2011:Q2 has been applied. We have applied tests for stationarity and co-integration and it has been discovered that there is a long-run co-integration relationship between money supply, stock prices and output. We have estimated both a VAR model and VEC model, and we have also generated impulse-response functions from the estimated VAR models, along with comparing the usefulness of VAR and VEC models for the real gross domestic product growth modelling. The evidence obtained from the analysis of time series suggests that in all cases we can discover the long-run relationships among variables applied. Money supply and stock market development have a certain predictive content for the real economic activity. When considering the results of the short-run analyses, we have to accept the great differences among countries. Based on the results of comparisons and evaluations of the VEC and the VAR models, we may state that VEC models are significantly better when the co-integrating relationships are enforced.